2015
DOI: 10.1183/13993003.00156-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lung disease on respiratory impedance in young children with cystic fibrosis

Abstract: This study aimed to evaluate the ability of the forced oscillation technique (FOT) to detect underlying lung disease in preschool children with cystic fibrosis (CF) diagnosed following newborn screening.184 children (aged 3-6 years) with CF underwent lung function testing on 422 occasions using the FOT to assess respiratory resistance and reactance at the time of their annual bronchoalveolar lavage collection and chest computed tomography scan. We examined associations between FOT outcomes and the presence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 43 publications
(68 reference statements)
2
23
1
Order By: Relevance
“…However, ROC analysis of impedance values obtained using impulse oscillometry demonstrated that no outcomes were capable of detecting which CF children displayed abnormal spirometry results . In addition, it has been shown that FOT outcomes do not reflect the progression of the underlying structural lung disease in cystic fibrosis . Our study does not have the ability to directly comment on the relationship between FOT data and physiological findings.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…However, ROC analysis of impedance values obtained using impulse oscillometry demonstrated that no outcomes were capable of detecting which CF children displayed abnormal spirometry results . In addition, it has been shown that FOT outcomes do not reflect the progression of the underlying structural lung disease in cystic fibrosis . Our study does not have the ability to directly comment on the relationship between FOT data and physiological findings.…”
Section: Discussioncontrasting
confidence: 73%
“…A diagnosis of cystic fibrosis was made following newborn screening and children recruited through CF clinics at Princess Margaret Hospital (Perth, Australia). FOT was performed during annual surveillance visits as detailed by Ramsey et al…”
Section: Methodsmentioning
confidence: 99%
“…Gangell et al found that on average CF children have higher Rrs and lower Xrs compared with reference values, and that CF children with current respiratory symptoms have higher Rrs and lower Xrs compared with asymptomatic children . Ramsey et al found that FOT outcomes were not sensitive to lung inflammation, pro‐inflammatory pathogens, structural lung abnormalities, or longitudinal progression of disease in a large cohort of pre‐school children with CF . Sakarya et al found that oscillatory mechanics differed between children with CF and healthy controls, that they got worse during exacerbation and improved after recovery …”
Section: Discussionmentioning
confidence: 99%
“…25 Ramsey et al found that FOT outcomes were not sensitive to lung inflammation, pro-inflammatory pathogens, structural lung abnormalities, or longitudinal progression of disease in a large cohort of pre-school children with CF. 26 Sakarya et al found that oscillatory mechanics differed between children with CF and healthy controls, that they got worse during exacerbation and improved after recovery. 27 We analyzed the association of within-breath changes in respiratory system impedance with other lung function parameters and lung morphology.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, the forced oscillation technique was found to be relatively insensitive for detecting lung disease in preschool children with CF, with similar results seen in 184 children 3–6 years of age who had pronounced respiratory disease measured by CT scan abnormalities and inflammatory mediators and in those without detectable lung disease. In addition, the progression of lung disease over 1 year was not associated with worsening forced oscillation technique outcomes …”
Section: Physiological Assessmentmentioning
confidence: 86%